Zero-field splitting in a series of structurally related mononuclear NiII-bispidine complexes - Atanasov, Mihail; Comba, Peter; Helmle, Stefan; Müller, Dennis (Inorganic chemistry, 2012)
The synthesis, single-crystal X-ray structures, electronic absorption spectra, and magnetic properties of six NiII complexes with a tetradentate (L1) and three pentadentate (L2, L3, L4) bispidine ligands (3,7-diazabicyclo[3.3.1]nonane derivatives), Ni(L1·H2O)(OH2)2](PF6)2, [Ni(L1·H2O)(O2NO)]NO3, [Ni(L1·H2O)(OOCCH3)]PF6, [Ni(L2·H2O)NCMe](PF6)2, [Ni(L3·H2O)OH2](PF6)2, and [Ni(L4·H2O)NCMe](PF6)2 are reported. The Ni-donor bonding to pyridine and tertiary amine groups and oxygen- or nitrogen-bound coligands, completing the octahedral coordination sphere of NiII, is analyzed using a combination of ab initio electronic structure calculations (complete active space self-consistent field, CASSCF, followed by N-electron valence perturbation theory, NEVPT2) and angular overlap ligand field analysis. Magnetic properties are rationalized with an analysis of the magnetic anisotropy in terms of zero-field splitting and g-tensor parameters, obtained from first principles, and their correlation with the NiII-donor bonding parameters from the ligand field analysis of the ab initio results. A two-dimensional spectrochemical series of the ligands considered, according to their σ and π bonding to NiII, is also derived.
Im Titel ist "II" hochgestellt
Gesehen am 20.08.2018